مكافحة تمويل الارهاب بين الاليات القانونية والصعوبات العملية - بلال زرايرية; سهيل بن يحي (My University, 2024)
Abstract The crime of financing terrorism is a serious crime and has even been classified as a terrorist crime. It contributes to supporting terrorist groups with various means and equipment. This crime is linked to several other crimes such as money laundering, organized crime, and others. Therefore, the international community has sought to develop legal mechanisms in order to combat this crime. Crime, through concluding international and regional agreements, most of which stipulate the establishment of international cooperation, and also obliges countries to establish national bodies concerned with financial transactions, by tracking the source and path of funds Suspicious crimes that may be a source of financing for terrorist organizations, since this crime is often linked to money. Countries have also resorted to establishing internal laws to combat the financing of terrorism at the national level, in addition to the security services that play an important role in maintaining the security of countries, but despite the presence of these mechanisms As for the efforts being made, terrorist financing remains a source of concern, due to the practical difficulties that stand in the way of these efforts. These difficulties are due to many reasons and factors that prevent the implementation of these mechanisms. .............................. ملخص المذكرة تعد جريمة تمويل الإرهاب جريمة خطيرة بل صنفت على أنها جريمة إرهابية، تساهم في دعم الجماعات الإرهابية بمختلف الوسائل و المعدات، و ترتبط هذه الجريمة بعدة جرائم أخرى مثل تبييض الأموال و الجريمة المنظمة و غيرها، لذلك سعى المجتمع الدولي إلى استحداث آليات قانونية قصد مكافحة هذه الجريمة، من خلال عقد الاتفاقيات الدولية و الإقليمية التي تنص معظمها على تكريس التعاون الدولي، كذلك تلزم الدول بإنشاء هيئات وطنية تعنى بالمعاملات المالية، ذلك من خلال تتبع مصدر و مسار الأموال المشبوهة التي قد تكون مصدرا لتمويل التنظيمات الإرهابية لكون هذه الجريمة ترتبط بالأموال في أغلب الأحيان، كما لجأت الدول إلى وضع قوانين داخلية لمكافحة تمويل الإرهاب على المستوى الوطني، إضافة إلى الأجهزة الأمنية التي تلعب دورا هاما في الحفاظ على أمن الدول، لكن رغم وجود هذه الآليات و الجهود المبذولة يبقى تمويل الإرهاب مصدر قلق، بسبب الصعوبات العملية التي تقف عائقا أمام هذه الجهود، و ترجع هذه الصعوبات إلى العديد من الأسباب و العوامل التي تحول دون تطبيق هذه الآليات . ............................. Résumé Le crime de financement du terrorisme est considéré comme un crime grave, classé même comme un crime terroriste. Il contribue au soutien des groupes terroristes par divers moyens et équipements. Ce crime est lié à plusieurs autres crimes tels que le blanchiment d'argent et le crime organisé. Pour cette raison, la communauté internationale a cherché à mettre en place des mécanismes juridiques pour combattre ce crime, en concluant des accords internationaux et régionaux qui consacrent principalement la coopération internationale. Ces accords obligent également les États à établir des organismes nationaux chargés des transactions financières, en traçant l'origine et le parcours de l'argent Les sources de financement suspectes pour les organisations terroristes sont souvent liées à des crimes liés à l'argent. Les pays ont mis en place des lois nationales pour lutter contre le financement du terrorisme, et les forces de sécurité jouent un rôle crucial dans la préservation de la sécurité nationale. Cependant, malgré ces mécanismes et les efforts déployés, le financement du terrorisme reste une préoccupation en raison des difficultés pratiques qui entravent ces efforts, attribuées à plusieurs raisons et facteurs qui entravent la mise en œuvre de ces mécanismes.